2020
DOI: 10.33365/jeltl.v1i2.604
|View full text |Cite
|
Sign up to set email alerts
|

What Is Your Favorite Movie?: A Strategy of English Education Students to Improve English Vocabulary

Abstract: Vocabulary is one of the most important language components in learning the English language. A vocabulary is several English words that are taught to students in the teaching and learning process which goes hand in hand with all four English skills, especially listening. By increasing vocabulary, students’ ability for better understanding in listening, speaking, reading, and writing will likely increase. The more they listen, the more words they will add to their mastering vocabulary. Moreover, many kinds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 0 publications
2
42
0
2
Order By: Relevance
“…There are various considerations, one of which is the accessibility of media that can ultimately support learning listening inside and outside the classroom. According to Simamora & Oktaviani (2020), many media can be used to hone listening skills, one of which is songs. From quantitative data, a large amount of students agree that English songs are suitable media for listening learning because they can access them anywhere and anytime.…”
Section: Discussionmentioning
confidence: 99%
“…There are various considerations, one of which is the accessibility of media that can ultimately support learning listening inside and outside the classroom. According to Simamora & Oktaviani (2020), many media can be used to hone listening skills, one of which is songs. From quantitative data, a large amount of students agree that English songs are suitable media for listening learning because they can access them anywhere and anytime.…”
Section: Discussionmentioning
confidence: 99%
“…Di samping itu, pelaksanaan strategi pembelajaran mendengarkan yang baik berikut tidak ter-tutup kemungkinan melibatkan kegiatan-kegiatan dalam ruang lingkup keterampilan berbicara dan menulis seperti demonstrasi, cerita pribadi, wawancara, bertelepon, bagan cerita atau story maps, survei kelompok, dan pidato singkat (Rost, 1991). Selain itu penggunaan media seperti film (Simamora & Oktaviani, 2020); (Sari & Aminatun, 2021) dan lagu (Lestary, 2019); (Hadi, 2019) juga dapat meningkatkan kemampuan mendengarkan dan kosa-kata (vocabulary) bahasa Inggris mereka. Pada Gambar 6, peserta pelatihan di Desa Perean diundang untuk melakukan kegiatan menyimak melalui cerita pribadi.…”
Section: Gambar 8 Praktik Menyimak Atau Listening Dalam Bahasa Inggrisunclassified
“…Meanwhile, other studies have shown that English movies can provide effective results in learning English vocabulary (Br Simamora & Oktaviani, 2020). Alternatively, through understanding word morphemes to find other word forms, as in the research conducted by (Varatharajoo et al, 2015).…”
Section: A the Limited Vocabularymentioning
confidence: 99%